Haggard’s Use of the Phoenician Analogy with Britain - John Coates (Cahiers Victoriens et Edouardiens)
In the late Victorian and Edwardian periods, several writers voiced their apprehensions about the state of the British Empire and the dangers they thought it faced by making comparisons between Britain and the Phoenician city of Tyre and the greatest of Tyre’s colonies, Carthage. This paper compares Rider Haggard’s use of this analogy in his novel Elissa or the Doom of Zimbabwe with other writers of his time who compared Britain to the Phoenicians. Haggard emerges as deeper, more wide-ranging and sophisticated in his use of the ‘Phoenician analogy’ than other writers who employed it.